2012
DOI: 10.1095/biolreprod.111.095349
|View full text |Cite
|
Sign up to set email alerts
|

The Industrial Chemical Bisphenol A (BPA) Interferes with Proliferative Activity and Development of Steroidogenic Capacity in Rat Leydig Cells1

Abstract: The presence of bisphenol A (BPA) in consumer products has raised concerns about potential adverse effects on reproductive health. Testicular Leydig cells are the predominant source of the male sex steroid hormone testosterone, which supports the male phenotype. The present report describes the effects of developmental exposure of male rats to BPA by gavage of pregnant and lactating Long-Evans dams at 2.5 and 25 μg/kg body weight from Gestational Day 12 to Day 21 postpartum. This exposure paradigm stimulated L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 67 publications
4
98
0
2
Order By: Relevance
“…These results are similar to those recently reported for maternal bisphenol A exposure, which appears to have comparable estrogenic effects on adult-type Leydig cell differentiation. 33 There is also a good correlation between the findings reported here and our recent study on the influence of DBP and DES upon adult-type Leydig cell regeneration following ethane dimethane sulfonate ablation, 4 where also the kinetics of Leydig cell differentiation was modulated by these xenobiotics.…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to those recently reported for maternal bisphenol A exposure, which appears to have comparable estrogenic effects on adult-type Leydig cell differentiation. 33 There is also a good correlation between the findings reported here and our recent study on the influence of DBP and DES upon adult-type Leydig cell regeneration following ethane dimethane sulfonate ablation, 4 where also the kinetics of Leydig cell differentiation was modulated by these xenobiotics.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, these preliminary studies suggest that low‐dose BPA has the potential to pose health hazards. Recent studies have also aimed to evaluate the role of BPA in carcinogenesis,7, 22, 23 and have indicated that exposure to BPA may account, at least partially, for the increased incidence of multiple cancers, including breast cancer,24, 25, 26, 27 ovarian cancer,28, 29 uterine cancer,30 prostate cancer,31, 32 testicular cancer,33 and liver cancer 34. The carcinogenic effects of BPA are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptors (ERs) are highly expressed as well as androgen receptors at male reproductive tract including Leydig cells (60,61). It is reported that estrogens are as important as androgens in male reproductive tract biology (62).…”
Section: Leydig and Sertoli Cellsmentioning
confidence: 99%
“…A number of researchers have reported that BPA has the ability to bind the estrogen receptor and bring about defects in the reproductive tract at studies in vitro rodent models (64)(65)(66). It is assumed that BPA has a higher affinity for ER-β but BPA can active ER-α and ER-β-mediated transcription process with comparable effectiveness in some tissues (61,67,68). Previous investigations have reported that BPA acts as an AR (Androgen Receptor) antagonist and can interact with ER-α and ER-β (69).…”
Section: Leydig and Sertoli Cellsmentioning
confidence: 99%
See 1 more Smart Citation